Analysis of Elderly Deaths in the Custodial Set-Up: A 10-year Retrospective Study - Bardale, Rajesh; Ninal, Nitin (Journal of Indian Academy of Forensic Medicine, 2022)
Death in a custodial setup is always a heart-rending moment for family members. Moreover, it raises doubt and distrust in the minds of near and dear ones whether such death is because of a natural cause or an unnatural act. The present study aimed to analyze the death of the elder population in a custodial setup (police and prison). This is a postmortem examination based retrospective study. A standard proforma was designed to collect the information to ensure consistency for the whole sample. Only elder inmate death was included in this study. A total of 119 autopsies in custodial setup (police and prison) were performed for 10 years from January 2009 to December 2018 out of which 34 (28.57%) cases were of an elder inmate. Amongst 34 elder inmates, 31 (91.17%) were male and 3 (8.82%) were female. The mean age was 70.4 years. Amongst all deaths, 33 (97.05 %) were because of natural causes. Myocardial infarction was the leading cause of death. The majority of the imprisoned people (91.17%) were male and most of them (85.29%) were convicted for the various offense. The present study had identified some features of elder deaths in custodial setup.